SEX-RELATED DIFFERENCES IN THE ANALGESIC RESPONSE TO THE RAT TAIL IMMERSION TEST - Molina, N.; Bedrandecastro, MTB; Bedrandecastro, J. C. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
The analgesic response was evaluated by the tail immersion test in adult male (N = 30), female (N = 21) and androgenized female Wistar rats (N = 15). The reaction time for tail withdrawal from the hot water bath was faster for male than for female rats (3.48 +/- 0.12 vs 6.46 +/- 0.42 s). The reaction time of androgenized female rats was similar to that of male rats (3.08 +/- 0.16 s). Blockade of opiate receptors with naloxone (2 mg/kg, ip) decreased the sensitivity to the noxious stimuli in males (4.08 +/- 0.10 s) and in androgenized females (3.69 +/- 0.19 s) but increased it in female rats (5.01 +/- 0.41 s). These data show sex-related differences in the analgesic response evaluated by the tail immersion test and indicate that administration of androgens to newborn female rats affects their pain sensitivity.
Keywords: PAIN; SEX DIFFERENCE; TAIL IMMERSION TEST; NEONATAL ANDROGENIZATION